Problem etike v delu Drugi spol Simone de Beauvoir - Švajncer, Marija (Anthropos (Ljubljana), 1998)
The article, The Problem of ethics in Simone de Beauvoir's work The second sex, concerns dilemmas and paradoxes arising from the study of women's issues; it is an issue with its distinctly ethical dimension, yet ethics itself is problematized there, for the woman-man relation is again a relationship in which conflicts and inequality are established. Throughout this article, there emerges an attempt to give arguments for a hypothesis that women's issues are assumed to be unsolvable, and that only partial "victories" are those which can be realized, while in the mental horizon of existentialism, all people are likely to be defeated. The assumed reasons for author's compehensive description, accumulation of facts, and interdisciplinarity in her work The second sex are also indicated
Keywords: Beauvoir, Simone de, 1908-1986; ethics; etika; etično; žensko vprašanje